L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis